Can explicit training in cued speech improve phoneme identification?. (2nd January 2017) - Rees, R.; Fitzpatrick, C.; Foulkes, J.; Peterson, H.; Newton, C.
ABSTRACT: When identifying phonemes in new spoken words, lipreading is an important source of information for many deaf people. Because many groups of phonemes are virtually indistinguishable by sight, deaf people are able to identify about 30% of phonemes when lipreading non-words. Cued speech (CS) is a system of hand shapes and hand positions used alongside speech to disambiguate similarities in lip patterns. Deaf children exposed to CS from under 3 years of age go on to develop age-appropriate language and literacy skills. However, there are no studies evaluating the explicit training of CS with older deaf children. This study is the first part of a long-term project to develop and evaluate a computer-delivered programme to teach school-aged deaf children to recognize cued phonemes. Sixty-two adult hearing participants were allocated to a single training session in one of three training conditions: cued speech training (CST), lipreading training and auditory training in noise. They were all tested on their ability to identify 13 phonemes in non-words when denied access to sound. The CST group made highly significant improvements in identifying cued phonemes and these changes could not be explained by lipreading practice or familiarization with a closed set of phonemes. Improvements generalized to non-words that were not used in training. This suggests that explicit training in CS could help deaf children to identify cued phonemes in new words. Practical implications of introducing the teaching of CS to selected deaf children are discussed.